Factors with a major effect on the budgetary control process: An empirical study from the Czech Republic - Jiří Dokulil; Boris Popesko; Kateřina Kadalová (Amfiteatru Economic Journal, 2022)
Superlatives are commonplace in descriptions of traditional budgeting. Within managerial accounting techniques, it is one of the most frequently used, the most researched, but also the most criticized. While academics are largely united in criticism of traditional budgeting practices due to their inflexibility and consumption of resources, the existing studies have not identified universal assumptions to improve this system. The inconsistent conclusions in current literature create a need to explore approaches to mitigation of budgetary weaknesses. Furthermore, this incomplete knowledge is an impulse to examine factors influencing the choice of these approaches. The authors conducted a review of the literature to amass information on approaches developed to enhance traditional budgeting methods. Subsequently, research was conducted on the extent of utilization and the subjective perception of such methods at a sample of companies operating in the Czech Republic. The authors additionally attempted to determine which factors influenced the decisions of managers in selection of such a tool. A web-based survey was devised with the aim of gathering data, followed by analysis of correlation between selected variables through application of Pearson's chi-square test. The literature review revealed the importance of conducting a budgetary review in improving the budgetary control. In total, 136 Czech companies took part in the survey, and it was discovered that a significant number of them had implemented traditional budgeting methods. More than 80% of respondents monitored any variation within their budgets. In the following part, the share of foreign capital was identified as the factor that influenced choices made in budgetary control. Since no correlation was discerned between revision of a budget and subsequent perception of its efficiency, the results lend support to arguments that minor improvements do not radically affect budgeting overall.
Keywords: M41; M19; 330; budgeting; planning; budget review; Czech businesses